Tanmiyat Mahārat al-Kalām bi Istifādat al-wasāʾil at-tafāʿuliyyah fī Darul Lughah Al Arabiyyah Aceh - Arini El-Haq; Neng Silvia; Aini Nur Sholehah; Sabrur Rahma (Uktub, 2025)
The aims of this research is to: (1) Describe the interactive methods used in teaching speaking skill, (2) describe the development of speaking skill by interactive methods, (3) reveal the supporting and obstacle factors for the development of speech skill by interactive media in Darul Lughah. This research used the case study method through a qualitative approach, and the data collected were analyzed by interview, observation, and documentation. The results are: (1) The interactive means used in teaching speaking skill in Darul Lughah are video clips or films, various attractive images and recorded audio. In addition, teachers need some devices to benefit from these means, including: the computer or mobile, monitor, speaker, and internet. (2) The development of speaking skill by interactive methods in Darul Lughah use closed-ended dialogue, open-ended dialogue, restricted or directed expression, free expression, drama, public speaking, watching, and debate. (3) The supporting factors for the development of speech skill by interactive media in Darul Lughah are the teachers’ background and their linguistic scientific and educational competencies, the books, teaching methods, students’ background, and Darul Lughah’s environment. The obstacles faced by teachers are the lack of skill of some teachers in using interactive tools, the unavailability of devices or their damage in some cases, and the low quality of the international network in some cases.